Present Bias in Choices over Food and Money - Alexander M. Danzer; Helen Zeidler (CESifo GmbH, 2024)
This paper investigates time inconsistencies in food consumption based on a field experiment at a college canteen where participants repeatedly select and consume lunch menus. The design features a convex non-monetary budget in a natural environment and satisfies the consume-on-receipt assumption. Leveraging 3,666 choices of different food healthiness, we find no time inconsistency at the meal level. Utility weight estimates at the dish level reveal that consumers balance healthiness between food categories. Individuals who exert self-control take up a commitment device as soon as available, while non-committers are present-biased. Dynamic inconsistencies in food and money choices are independent.
Keywords: D12; D01; C93; D91; I12; 330; field experiment; dynamic inconsistency; commitment; food consumption